Goodwill Impairment: An Empirical Investigation of Write-Offs under SFAS 142 - Thorsten Sellhorn (Peter Lang International Academic Publishers, 2004)
In 2001, goodwill amortization in the US was eliminated in favor of an impairment-only approach, which, according to critics, gives managers vast discretion and opportunities for earnings management. Prior research suggests that discretionary asset write-offs are associated with economic factors and managers' financial reporting objectives. Based on a systematic literature review, this study investigates for a comprehensive sample of US firms the determinants of goodwill write-off behavior. Regression analysis shows that write-off behavior is significantly explained by firms' economic properties. Only in large, high-profile firms, incentives appear to be significant determinants. These findings suggest that the impairment-only approach does capture goodwill impairment at least to some extent.
Keywords: 330